Do the Best Scholars and Economists Attract the Highest Speaking Fees? - Ho Fai Chan; Bruno S. Frey; Jana Gallus; Markus Schaffner; Benno Torgler; Stephen Whyte (Center for Research in Economics, Management and the Arts (CREMA), 2013)
External prominence (measured by the number of pages indexed on search engines or TED talk invitations) can be capitalized on the speakers' market while research performance (measured by publication and citation indicators) cannot. There is thus a clear distinction between the capitalization of external and internal prominence. Success through authorship of books is also positively correlated with speaking fees, however once we control for external prominence the statistical significance disappears. We find that academics profit from having been awarded a major book prize.
Keywords: A11; A13; Z18; Z19; 330; Academic Performance; Scholarly Importance; Market for Economists; Social Importance of Economists; External and Internal Influence; Book Prizes; TED Talks